2008
DOI: 10.1128/aac.01509-07
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Response and Outcome of Infection with Salmonella enterica Serotype Typhi with Decreased Susceptibility to Fluoroquinolones: a United States FoodNet Multicenter Retrospective Cohort Study

Abstract: Patients with typhoid fever due to) were compared with patients infected with isolates with ciprofloxacin MICs <0.12 g/ml for fever clearance time and treatment failure. Of 71 patients, 30 (43%) were female and 24 (34%) were infected with Salmonella serotype Typhi with DCS; the median age was 14 years (range, 1 to 51 years). Twenty-one (88%) of 24 isolates with DCS were resistant to nalidixic acid. The median antimicrobial-related fever clearance times in the DCS and non-DCS groups were 92 h (range, 21 to 373 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
115
0
5

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(129 citation statements)
references
References 22 publications
9
115
0
5
Order By: Relevance
“…In vitro studies have shown that it is more potent than traditional first-line drugs and other macrolides against Salmonella spp. with an average MIC of 8μg/ mL (range 4 to 16μg/mL) [9].There are no reports of resistance of S. Typhi to azithromycin, and recent studies have shown that it is effective both clinically and bacteriologically in treating enteric fever even in those caused by MDR strains [6]. So, the present study was conducted to compare the efficacy and safety of azithromycin with ofloxacin in patients with uncomplicated typhoid fever.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In vitro studies have shown that it is more potent than traditional first-line drugs and other macrolides against Salmonella spp. with an average MIC of 8μg/ mL (range 4 to 16μg/mL) [9].There are no reports of resistance of S. Typhi to azithromycin, and recent studies have shown that it is effective both clinically and bacteriologically in treating enteric fever even in those caused by MDR strains [6]. So, the present study was conducted to compare the efficacy and safety of azithromycin with ofloxacin in patients with uncomplicated typhoid fever.…”
Section: Introductionmentioning
confidence: 96%
“…These strains are associated with point mutations in the gyrA gene and occasionally the parC gene [5]. Enteric fever caused by S. Typhi strains with an elevated MIC to ciprofloxacin and ofloxacin have been coupled with the failure of treatment with these antimicrobials and increased disease severity [6]. There are also reports from the Indian subcontinent of isolates that are fully resistant to fluoroquinolones and the extended spectrum cephalosporins [7].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical relevance of these strains was not evaluated in any of the previous studies [11][12][13]; however, one can assume therapeutic failure in these cases, as also seen with the nalidixic acid resistant strains with decreased ciprofloxacin susceptibility [19].…”
Section: Discussionmentioning
confidence: 99%
“…Studies from the United Kingdom, United States, and Kuwait [11][12][13] reported a higher percentage of discordant nalidixic acid and ciprofloxacin susceptibility results in their Southeast Asian immigrants or travellers (i.e., 7%, 12.5%, and 13.8%). Cooke et al report 5% S. Typhi isolates from Pakistan with discordant results [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation